European Carbon Uptake has Not Benefited From Vegetation Greening - Xuebang Liu; Bin He; Lanlan Guo; Ling Huang; Wenping Yuan; Xiuzhi Chen; Xingming Hao; Xiaoming Xie; Yafeng Zhang; Ziqian Zhong; Tiewei Li; Aifang Chen (Geophysical Research Letters)
Abstract Substantial evidences indicate a widespread increase in European vegetation greenness since the 1980s due to CO2 fertilization effects (eCO2) and climate warming, but the impact of this process on the regional terrestrial carbon cycle has not been systematically evaluated. Using empirical models based on eddy covariance and process‐based models, we found that the widespread greening did not contribute to an increase in European carbon uptake (decrease in net ecosystem exchange) with a non‐significant trend from 2000 to 2018. The greening‐associated increase in gross primary productivity (GPP) is offset by the simultaneous increase in ecosystem respiration (TER). Moreover, frequent heatwaves cause stronger reductions in GPP than TER, preventing the increase of carbon uptake. These results reveal the double‐edged sword effect of warming on European ecosystems and will help constrain regional models.